Orthopaedic Oncology Primary and Metastatic Tumors of the Skeletal System - Peabody, Terrance D.; Attar, Samer (Cancer Treatment and Research, 2014)
This text provides a comprehensive overview of orthopaedic oncology - the field of orthopaedic surgery that specializes in the evaluation and treatment of bone and soft tissue tumors of the musculoskeletal system. The opening chapters cover musculoskeletal imaging interpretation and the principles of musculoskeletal biopsy. Assessment and treatment of the full range of tumors are then described in a series of well-illustrated chapters. Detailed consideration is given to benign tumors, osteosarcomas, Ewing sarcomas, chondrosarcomas, metastatic bone disease of the axial and appendicular skeleton, and soft tissue sarcomas. This book will be invaluable for both orthopaedic surgeons and medical oncologists, providing a framework for understanding the fundamentals of these tumors and a sound basis for their treatment.